If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(p + 8) = 0 Reorder the terms: 6(8 + p) = 0 (8 * 6 + p * 6) = 0 (48 + 6p) = 0 Solving 48 + 6p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + 6p = 0 + -48 Combine like terms: 48 + -48 = 0 0 + 6p = 0 + -48 6p = 0 + -48 Combine like terms: 0 + -48 = -48 6p = -48 Divide each side by '6'. p = -8 Simplifying p = -8
| -90-6x=48-12x | | -4(-3x-8)-4x+8= | | 6(p+8)= | | x+28500-y=371500 | | 6(p+8)= | | x+28500-y=371500 | | 15/30=6/x | | 7x=3(3x-4) | | 7x=3(3x-4) | | 7x=3(3x-4) | | 175*20+25= | | -4=2/3m+6 | | -6x+7(-2x+6)=142 | | x+28500-x=371500 | | -4[p+1]=-2[8-2p] | | p+26.3=12.74 | | 18-50= | | v/4-2=8 | | x+28500-x=371500 | | -16+3x=x+4x | | p+26.3=12.74 | | x+28500-x=371500 | | -6x+7(-2x+6)=142 | | [(2x-45-20)2]-5=0 | | 18-50= | | -4[p+1]=-2[8-2p] | | 175*20+25= | | 7/915/8 | | 7+2x-8=1+2(x-1) | | 7/915/8 | | 7+2x-8=1+2(x-1) | | 7/915/8 |